2019
DOI: 10.1111/php.13087
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Photoprotective Activity of a Short‐term Ingestion of High‐Flavanol Cocoa: A Nutritional Intervention Study

Abstract: In vivo and in vitro studies have shown that prolonged oral administration of flavanol-rich cocoas extracts have photoprotective effects. The aim of the present study was to assess the photoprotective activity of short-time administration of a new variety of naturally selected cocoa extract rich in bioactive compounds. We selected a cocoa powder particularly rich in polyphenols, flavanols, caffeine, theobromine and theophylline. We then investigated, in 10 healthy subjects, the photoprotective effects of one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Cocoa polyphenols have effective antioxidant and anti-inflammatory properties, interacting with various relevant pathways associated with several health advantages. For instance, flavanol-rich cocoa and cocoa derivatives increase nitric oxide (NO) synthesis, augment flow-mediated dilation (FMD) and enhance microcirculation [ 2 , 3 ], induce vasodilation and reduce blood pressure [ 4 ], attenuate platelet aggregation and improve endothelial and vascular function [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa polyphenols have effective antioxidant and anti-inflammatory properties, interacting with various relevant pathways associated with several health advantages. For instance, flavanol-rich cocoa and cocoa derivatives increase nitric oxide (NO) synthesis, augment flow-mediated dilation (FMD) and enhance microcirculation [ 2 , 3 ], induce vasodilation and reduce blood pressure [ 4 ], attenuate platelet aggregation and improve endothelial and vascular function [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, a clinical trial spanning over 12 weeks reported that a daily intake of 329 mg cocoa flavanols reduced UV-induced erythema by 25%, whereas a lower intake (27 mg) did not [151]. Other studies exploring shorter and longer intervention periods (1 and 24 weeks, respectively) had similar outcomes, resulting in increases in MED [150,152]. However, two studies investigated the effects of a higher dose (600 mg) over 12 weeks, and only one of these studies found a protective effect [153,154], suggesting that more research is needed to clarify the photoprotective effects of cocoa flavanols.…”
Section: Cocoa Flavanolsmentioning
confidence: 99%
“…Cocoa extract is a flavonoid that appears to confer dose‐dependent photoprotection (Table 3). 28 In a study by Heinrich et al 29 . participants were treated with either high‐ or low‐flavonol cocoa powder for 12 weeks.…”
Section: Flavonoidsmentioning
confidence: 99%